A Conceptual Framework Of Reconfigurable Conveyor System To Support Changeability In Manufacturing - Mohamad, Nor Rizan (2019)
Reconfigurable concept has a demand in the manufacturing system in order to support unpredictable customer demand. It is also to improve the changeability and functionality of the system to reduce time and cost-saving. A conveyor system is one of automated material handling systems commonly used in manufacturing industries. Due to the problem such as dynamic nature, space available, and risk operation, these conveyor systems are unable to suit the current market requirement. Therefore, this research aimed to propose a new conceptual framework of Reconfigurable Conveyor System (Re-Con) in order to support the changeability in the manufacturing system. At the end of the study, some case study is carried out to analyze and validate the concept. The study includes both conceptual framework for physical configuration and logical configuration. There are four possible configurations which are closed-loop, L-Shaped, U-Shaped and Straight-Line layout arrangement. For the logical configuration, there are six different modules of Programmable Logic Controller with different control strategies. The program is designed by using IEC 61131 Protocol. Function Block is designed from the program of each controller to make it easier to upload, download, design and redesign the controller when a changeable of layout arrangement is happen. The proposed conceptual framework is validated by using a lab-scale Re-Con. The analysis is conducted by using Maynard Operation Sequence Technique (MOST) analysis and Single Minutes Exchange Die (SMED). The physical configuration of Re-Con takes about 108.42 minutes and the logical configuration of Re-Con takes about 445.69 seconds compared to the lab-scale of the existing conveyor system. From the result, the development of the Reconfigurable Conveyor System can be made in the future study because it can reduce cost saving and time. In conclusion, the research’s objective to develop a conceptual framework of Re-Con has been achieved.